The ALERRT® instrument: a quantitative measure of the effort required to compromise prescription opioid abuse-deterrent tablets. (4th May 2017) - Cone, Edward J.; Buchhalter, August R.; Lindhardt, Karsten; Elhauge, Torben; Dayno, Jeffrey M.
ABSTRACT: Background : US FDA guidance recommends measuring the degree of effort needed to manipulate abuse-deterrent (AD) opioids. The ALERRT ® instrument (PinneyAssociates; Bethesda, MD) uses visual analog scales to assess the labor, effort, and resources necessary to physically compromise AD product candidates in standardized settings. Objective : Use the ALERRT ® instrument for testing morphine abuse-deterrent, extended-release, injection-molded tablets (ADER-IMT) 60 and 100 mg and the comparators immediate-release (IR) morphine sulfate 30 mg and extended-release (ER) morphine sulfate 60 mg. Methods : Four technicians tested the products using 10 household tools. The ALERRT instrument quantified effort (all tools) and time (3 preselected tools) required for manipulation. Results : Morphine-ADER-IMT 60 and 100 mg were difficult to manipulate, as demonstrated by high scores (mean range, 71.0−99.0 and 77.0−99.5, respectively). IR and ER morphine sulfate were easy to manipulate (low scores; mean range, 2.0−14.8 and 2.3−17.5, respectively). Statistically significant mean differences between morphine-ADER-IMT and comparators' ALERRT scores were observed. Manipulations of morphine-ADER-IMT 60 and 100 mg for 300 seconds failed to produce substantial powdering. Manipulations of IR morphine sulfate (mean range, 65.5−175.8 seconds) and ER morphine sulfate (49.3−163.0 seconds) produced substantial to complete powdering in 92% of tablets. Conclusions : Morphine-ADER-IMT was extremely difficult to manipulate versus non-AD formulations of morphine. The ALERRT system differentiated the degree of effort for manipulation of morphine-ADER-IMT and non-AD morphine formulations, indicating sensitivity of this instrument as part of Category 1 testing. By measuring the degree of effort required for manipulation, the ALERRT instrument provides an empirical assessment into the relative difficulty of manipulating opioid analgesics for abuse.